2013
DOI: 10.1039/c2nr32798h
|View full text |Cite
|
Sign up to set email alerts
|

Rolled-up magnetic microdrillers: towards remotely controlled minimally invasive surgery

Abstract: Self-folded magnetic microtools with sharp ends are directed at enabling drilling and related incision operations of tissues, ex vivo, in a fluid with a viscosity similar to that of blood. These microtools change their rotation from a horizontal to a vertical one when they are immersed into a rotational magnetic field. Novel self-assembly paradigms with magnetic materials can enable the creation of remotely controlled and mass-produced tools for potential applications in minimally invasive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
214
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(217 citation statements)
references
References 31 publications
2
214
0
1
Order By: Relevance
“…The targeted delivery of drugs can be achieved with the assistance of microswimmers [16,66], which are able to move against blood stream. Helical magnetic structures made by micro-origami techniques can function as microdrillers to remove blood clogs in the veins when remotely activated by a rotating magnetic field [67]. Microgrippers and magnetic tweezers take advantage of self-folding of micro-origami patterns, as mentioned in the introduction [29].…”
Section: Prospective Applicationsmentioning
confidence: 99%
“…The targeted delivery of drugs can be achieved with the assistance of microswimmers [16,66], which are able to move against blood stream. Helical magnetic structures made by micro-origami techniques can function as microdrillers to remove blood clogs in the veins when remotely activated by a rotating magnetic field [67]. Microgrippers and magnetic tweezers take advantage of self-folding of micro-origami patterns, as mentioned in the introduction [29].…”
Section: Prospective Applicationsmentioning
confidence: 99%
“…The magnetic layer also allows the utilization of the microtubes as micro-/nanodrillers [10,21]. In addition, the shape of the tubular micromotors can be altered to be slightly conical with a sharp tip when thin films are deposited on trapezoidal photoresist structures.…”
Section: Inorganic Microjets From Rolled-up Nanomembranesmentioning
confidence: 99%
“…In addition, the shape of the tubular micromotors can be altered to be slightly conical with a sharp tip when thin films are deposited on trapezoidal photoresist structures. This leads to the ability of the drillers to make incisions in cells and tissue [21]. It was demonstrated that microjets are powerful enough to swim in a controlled manner against flow in microfluidic channels [22,23].…”
Section: Inorganic Microjets From Rolled-up Nanomembranesmentioning
confidence: 99%
“…Moreover, they can be controlled precisely using external sources such as magnetic fields, ultrasound or light [20]. For example, they have been used to isolate cells [21], perform microbiopsies [22], sense proteins [23], ligands or other molecules of interest, deliver drugs or even help sperms with motion deficiencies to reach the oocyte, all in vitro [24][25][26][27]. Nonetheless, it is worth noting that the use of these new systems entails additional difficulties, such as their control and visualization in deep tissue in real time [28].…”
mentioning
confidence: 99%